Search for potential hypoglycemic agents among potassium salts of 3-benzyl-8-substituted xanthines - K. V. Aleksandrova; Ye. S. Pruhlo; Ye. K. Mykhalchenko; O. S. Shkoda; O. Yu. Cherchesova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Nowadays, the prevalence of metabolic syndrome (MS) is a serious problem among the world’s population. Metabolic syndrome includes the so-called “deadly” quartet – hypertension, type 2 diabetes mellitus (diabetes mellitus), dyslipidemia and alimentary obesity.